دراسة النقد الأدبي للأصالة الفكرية في النصوص العربية النيجيرية خلال القرن العشرين الميلادي - Khalil Mohammad Usman Gbodofu (Nady Al-Adab : Jurnal Bahasa Arab, 2021)
الملخص لايستغني أي عمل أدبى عن ناقد يوضح أغراضه ويبين قيمته، ولا يفهم أي قارئ مضامين الأدب وأسراره فهما صحيحا إلا بعملية التمييز بين الجيد والردئ. والنقد الأدبى نشاط فكري، ودراسة للآثار الأدبية وتقويمها، وعلماء اللغة العربية فى نيجيريا بذلوا جهدهم الكبير فى تحصيل هذا النشاط وتطوير هذه الدراسة، وتأثّروا كثيرًا بالنقاد العرب القدماء والمحدثين، وخاصة عند دراساتهم للانتاجات العربية التى يصدرها أهالى بلادهم، ولعل قضايا الأفكار والأساليب والموسيقى مما نال نصيب الأسد فى دراساتهمللأدب العربى النيجيري. ولهذا يود هذا البحث أن يلقي الضوء على اتجاهات علماء نيجيريا النقدية حول مسائل الصحة والخطأ، والابتكار والتقليد، والدين والخلق معتمدًا فى ذلك كله على المراجع الخارجية والداخلية، وعلى المخطوطات العربية فى نيجيريا بصفة خاصة. الكلمات المفتاحية: النقد الأدبي; الآثار الأدبية;  الأدب العربي النيجيري. Abstract: There is no any literary work that would be free from a critique that would explore its objectives and explain it’s values. Thus, no reader would comprehend the facts and figures of literature in its real sense except with the art of separating good from the bad. Literary criticism is an intellectual activity, the study of literary monuments and it’s correction. The Nigerian Arabic Scholars have contributed immensely in actualizing and developing this activity as a result of the impact of the old and recent Arab critiques on them, especially in the study of the output of their local writers. Perhaps, the theories of: thoughts, styles, and musics are at the fore front in their study of Nigeria Arabic literature. This is the reason this paper intends to    shed light on the critical direction of Nigeria Arabic scholars towards the issue of accuracy and inaccuracy, innovation and imitation, religion and behavior with reliance on the local and international sources, and also on Arabic Manuscript in Nigeria in particular. Keywords: Arab Critiques Theories; Literary Works; Nigerian Arabic Literary.